1996
DOI: 10.1093/oxfordjournals.esr.a018177
|View full text |Cite
|
Sign up to set email alerts
|

The changing meaning of cohabitation and marriage

Abstract: "In the Netherlands, the social meaning of both marriage and cohabitation has changed. Cohabitation started as an alternative way of living, developed into a temporary phase before marriage, and finally became a strategy for moving into a union gradually.... This article addresses the question whether or not individual past and current life-course experiences become increasingly important in explaining the differentiation of entry into marriage across female birth cohorts, and yet become decreasingly important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
94
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 18 publications
0
94
0
2
Order By: Relevance
“…For men, the mean age at first marriage was 28 in 1950, reached a low of 24.6 in the early 1970s, and increased again to 29 in the 1990s (Kalmijn 1994a). About two-thirds of couples now live together before they marry and there are few cohabiting couples who remain unmarried for long (Liefbroer 1991;Manting 1996;De Graaf and Steenhof 1999). Second, the Netherlands has experienced the same trend towards more egalitarian gender roles that other countries have experienced.…”
Section: Introductionmentioning
confidence: 99%
“…For men, the mean age at first marriage was 28 in 1950, reached a low of 24.6 in the early 1970s, and increased again to 29 in the 1990s (Kalmijn 1994a). About two-thirds of couples now live together before they marry and there are few cohabiting couples who remain unmarried for long (Liefbroer 1991;Manting 1996;De Graaf and Steenhof 1999). Second, the Netherlands has experienced the same trend towards more egalitarian gender roles that other countries have experienced.…”
Section: Introductionmentioning
confidence: 99%
“…Ряд информантов (№3, 5,15,19,20) были включены сразу в несколько групп ввиду смысловой многомерности их историй, в которых просматривалась многоаспектность мотивов перехода от статуса сожительства к официальному брачному статусу. Если обратиться к концепциям, которые базируются на идее, что активность индивида всегда ограничена определенными структурными рамками (теории Э. Гидденса, П. Бурдье, А. Шюца), то можно допустить, что мотивы сожителей к получению официального брачного статуса формируются в рамках определенной социальной действительности.…”
Section:  «в настоящее время легче отдыхать семьёй за границей: не нunclassified
“…Studies in the United States and Europe have indicated a wide range of reasons for cohabiting, which include the desire to spend more time together, testing a relationship, financial benefits, convenience and housing issues (Haskey, 2001b;McRae, 1997;Rhoades, Stanley, & Markman, 2009;Sassler, 2004;Seltzer, 2004). As social pressures for couples to marry decline, cohabitation has become less of a prelude to marriage and more of a permanent living arrangement parallel to marriage in which children may be raised (Bumpass & Lu, 2000;Bumpass, Sweet, & Cherlin, 1991;Manting, 1996).…”
mentioning
confidence: 99%
“…Cohabitation rates have increased over the last few decades in both the United States and Europe (Haskey, 1999;Manting, 1996;Seltzer, 2004). In the UK, the proportion of couples that lived together before marrying increased from 2% in the mid 1960s to 70% in the mid 1990s, while the proportion of children born out of wedlock increased from 5% to 35% over the same period (Haskey, 2001a).…”
mentioning
confidence: 99%
See 1 more Smart Citation